2015
DOI: 10.1371/journal.pone.0145419
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of Glycosylation of Recombinant Human Platelet-Derived Growth Factor-BB in Pichia pastoris

Abstract: Yeast Pichia pastoris is a widely used system for heterologous protein expression. However, post-translational modifications, especially glycosylation, usually impede pharmaceutical application of recombinant proteins because of unexpected alterations in protein structure and function. The aim of this study was to identify glycosylation sites on recombinant human platelet-derived growth factor-BB (rhPDGF-BB) secreted by P. pastoris, and investigate possible effects of O-linked glycans on PDGF-BB functional act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…However, in contrast to the glycosylation system of mammalian cells, yeast cells have a mannose-rich glycosylation system; thus, they are often not suitable for use in medicine. In particular, post-translational modifications such as glycosylation in Pichia pastoris often lead to unexpected protein structure and function (Dai et al, 2015 ). Nevertheless, C. glutamicum may be advantageous as a host for the expression of antibody fragments such as the scFv and Fab (antigen-binding fragment), which do not require glycosylation (Yim et al, 2014 ).…”
Section: Secretions Of Proteins From C Glutamicummentioning
confidence: 99%
“…However, in contrast to the glycosylation system of mammalian cells, yeast cells have a mannose-rich glycosylation system; thus, they are often not suitable for use in medicine. In particular, post-translational modifications such as glycosylation in Pichia pastoris often lead to unexpected protein structure and function (Dai et al, 2015 ). Nevertheless, C. glutamicum may be advantageous as a host for the expression of antibody fragments such as the scFv and Fab (antigen-binding fragment), which do not require glycosylation (Yim et al, 2014 ).…”
Section: Secretions Of Proteins From C Glutamicummentioning
confidence: 99%
“…[ 15 ] Other studies, however, suggest that P. pastoris can produce proteins with O‐glycans consisting of 6‐Man. [ 16,17 ] These mannose residues are mostly α‐1,2 or β‐linked, and they can also be phosphorylated. [ 4 ] β‐linkages on recombinant glycoproteins could cause an immunogenic response in humans due to interaction with the mannose receptor, or dendritic cell‐specific intercellular adhesion molecule‐3‐grabbing non‐integrin (DC‐SIGN).…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that this could be either due to the absence of highly immunogenic terminal α‐1,3‐mannosyl groups, or due to lower complexity of mannose type O ‐glycans in P. pastoris compared to more complex ones in mammalian cells. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the absence of glycosylation in prokaryotic expression systems like Escherichia coli , glycosylation is common in eukaryotic host systems (i.e., Pichia pastoris ) and play important roles in proper folding, transport, and stability of proteins [ 23 , 34 – 38 ]. Yeast strains are widely used for recombinant protein production, during which both O - and N -glycosylations occur preceding protein secretion and have obvious effects on enzyme properties [ 39 41 ]. P. pastoris is capable of adding both O - and N -linked carbohydrate moieties to secreted proteins.…”
Section: Introductionmentioning
confidence: 99%